Herpes Zoster Reactivation Following COVID-19 mRNA Vaccination in an Elderly Patient: A Case Report - Sarah, Ratu Siti Khadijah; Hapsari, Yari Castiliani; Yusharyahya, Shannaz Nadia; Miranda, Eliza; Edwar, Sarah Qanita (Journal of General - Procedural Dermatology and Venereology Indonesia, 2025)
Background: Latent varicella-zoster virus (VZV) in nerve ganglia may reactivate into herpes zoster infection. The coronavirus disease (COVID-19) vaccine is suspected of triggering VZV reactivation, although the exact cause is unclear. This case report aims to raise awareness of the potential complications induced by the COVID-19 mRNA vaccine, particularly in elderly patients. Case Illustration: A 62-year-old woman complained of itchy and painful unilateral dermatomal herpetiform blisters six days after mRNA COVID-19 vaccination. The vesicle first appeared on the left breast, spreading to the back. The patient has a history of hypertension. After the administration of 800 mg of acyclovir five times a day for seven days, the vesicles dried up, and no new vesicles emerged. Discussion: The incidence of herpes zoster has been widely reported to occur within 5-7 days after the COVID-19 vaccination, mostly due to the mRNA vaccine. The dysregulated cell-mediated immune system may trigger VZV reactivation. The vaccines have been shown to induce a cellular response with increased CD8+ T-cells and T-helper type 1 CD4+ T cells. The VZV-specific CD8+ cells cannot control VZV after the massive shift of naïve CD8+ T-cells in the setting of COVID-19 vaccination. Hypertension is also allegedly the main comorbid factor for herpes zoster reactivation after COVID-19 vaccination. Conclusion: Increased awareness and early recognition of potential COVID-19 vaccine-related complications, especially in elderly individuals with comorbidities, are important for timely management and prevention of further issues.